Guest

If x, y, z are in A.P. and tan^ -1x, tan^ -1y and tan ^-1z are also in A.P., then (1) 2x = 3y = 6z (2) 6x = 3y = 2z (3) 6x = 4y = 3z (4) x = y = z

If x, y, z are in A.P. and tan^ -1x, tan^ -1y and tan ^-1z are also in A.P., then
(1) 2x = 3y = 6z
(2) 6x = 3y = 2z
(3) 6x = 4y = 3z
(4) x = y = z

Grade:11

2 Answers

Saurabh Koranglekar
askIITians Faculty 10341 Points
2 years ago
Dear student

Please attach the image of the question

Regards
Vikas TU
14149 Points
2 years ago
Dear student 
Question is not clear 
Please attach an image, 
We will happy to  help you 
Good Luck
Cheers
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free